Global positioning : - Samama, Nel (Wiley-Interscience, 2008)
Global Positioning presents an overview of the strengths and weaknesses of various systems with a specific emphasis on those that are satellite-based. Beginning with a description of the evolution of positioning systems, the book provides detailed coverage of the three main Global Navigation Satellite System (GNSS) constellations, discusses how to cope with indoor positioning, defines development activities and commercial positioning, and proposes a vision for the future of the field.